Host Country Sourcing of Multinational Enterprises: A Corporate Social Responsibility Perspective - Jung, Jae C. (Journal of business ethics, 2018)
Through corporate social responsibility (CSR) activities, a firm can develop the capability for managing and benefiting from stakeholder relationships. This study refers to such a capability as stakeholder influence capacity (SIC). In a host country, locally sourcing parts and/or materials can generate economic value and improve social welfare. Moreover, local sourcing provides opportunities for a foreign firm to apply and advance SIC while closely interacting with host-country stakeholders. Accordingly, we expect that a firm, having gained SIC through CSR activities in its home country, will be more likely to source parts and/or materials in the host country. We also expect that the relationship between SIC (gained from CSR in the home country) and host-country sourcing is conditional upon a foreign firm’s intangible resources and liabilities of foreignness. Our empirical analysis, using Korean datasets, supports the positive relationship between CSR and local sourcing. We find that this positive relationship is more pronounced either when the firm is committed to technology development or when its home and host countries are geographically or culturally distant.